The Effect of Endorphin Massage on the Intensity of Dysmenorrhea in Adolescent Girls - Jama, Fatma; Mahmud, Azrida; Najihah, Najihah; Nurmagfirah, Iffah; Hikmah, Nur Asia; Sunarti, Sunarti (Jambura Nursing Journal, 2024)
Dysmenorrhea is often experienced by young women, this can disturb your sense of comfort and interfere with daily activities, generally it is not dangerous but must be treated immediately. Dysmenorrhea usually occurs before or during menstruation, starting from one to two days before menstruation or during menstruation. Dysmenorrhea treatment can be divided into two categories, namely pharmacological and non-pharmacological. Pharmacological treatment such as consuming non-steroidal anti-inflammatory drugs (NSAIDs), while non-pharmacological treatment can be done with Endorphin Massage. Endorphin Massage has the effect of stimulating the body to release endorphin compounds which are pain relievers and can create a feeling of comfort, which is a therapeutic action that is useful for improving physical and psychological conditions. The aim of the research was to determine the effect of giving endorphin massage on reducing dysmenorrhea in young women. The research design used was Quasi Experimental with a pre-experimental design, with one group pretest-posttest. to see the effect of Endorphin Massage before and after the intervention. The sample size was 30 respondents. The sampling technique used consecutive sampling which had been adjusted to the inclusion criteria and exclusion criteria. This study used the Wilcoxon statistical test with a significance level of Î± = 0.05. The results of this study showed a value of Ï = 0.000, where the value of Ï